2016
DOI: 10.1371/journal.pone.0155516
|View full text |Cite
|
Sign up to set email alerts
|

A Calsequestrin-1 Mutation Associated with a Skeletal Muscle Disease Alters Sarcoplasmic Ca2+ Release

Abstract: An autosomal dominant protein aggregate myopathy, characterized by high plasma creatine kinase and calsequestrin-1 (CASQ1) accumulation in skeletal muscle, has been recently associated with a missense mutation in CASQ1 gene. The mutation replaces an evolutionarily-conserved aspartic acid with glycine at position 244 (p.D244G) of CASQ1, the main sarcoplasmic reticulum (SR) Ca2+ binding and storage protein localized at the terminal cisternae of skeletal muscle cells. Here, immunocytochemical analysis of myotubes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…CASQ1 mediates skeletal muscle development and contraction . CRYAB has negative regulation of cell growth and organ development .…”
Section: Discussionmentioning
confidence: 99%
“…CASQ1 mediates skeletal muscle development and contraction . CRYAB has negative regulation of cell growth and organ development .…”
Section: Discussionmentioning
confidence: 99%
“…D244G (a heterozygous missense mutation in the CASQ1 gene) was the first identified CASQ1 mutant in patients showing mild myopathy characterized by muscle weakness, fatigue, and the presence of large vacuoles [165][166][167] . D244G induces misfolding and abnormal aggregation of CASQ1 (which is different from the physiological CASQ1 polymers) due to the loss of the electric charge in D244 that is involved in the Ca 2+ -binding and Ca 2+ -dependent polymerization of CASQ1.…”
Section: Casq1-related Diseasesmentioning
confidence: 99%
“…In 2014, Rossi et al 5 reported the first CASQ1 mutation, c.731A > G (p.Asp244Gly) in eight patients characterized by mild proximal weakness, fatigue, and large vacuoles containing aggregation of SR proteins. Subsequently, Lewis et al, 10 D'Adamo et al 11 and Semplicini et al 9 identified the similar phenotype in patients with c.731A > G (p.Asp244Gly). In these patients, sarcoplasmic vacuolar aggregations and reduced Ca 2+ release from the SR induced by abnormal CASQ1 aggregates were observed.…”
Section: Discussionmentioning
confidence: 92%